Influence of Ion Strength and pH on Thermal Stability of Yeast Formate Dehydrogenase - Tishkov, V.I. (A.I. Gordeyev, 2010)
The kinetics of the thermal inactivation of recombinant wild–type formate dehydrogenase from Candida boidinii yeast was studied in the temperature range of 53–61(o)C and pH 6.0, 7.0, and 8.0. It was shown that the loss of the enzyme’s activity proceeds via a monomolecular mechanism. Activation parameters ∆Н() and ∆S() were calculated based on the temperature relations dependence of inactivation rate constants according to the transition state theory. Both parameters are in a range that corresponds to globular protein denaturation processes. Optimal conditions for the stability of the enzyme were high concentrations of the phosphate buffer or of the enzyme substrate sodium formate at pH = 7.0.